2020
DOI: 10.1210/jendso/bvaa083
|View full text |Cite
|
Sign up to set email alerts
|

A New Insight into the Surgical Treatment of Primary Macronodular Adrenal Hyperplasia

Abstract: Purpose This prospective study presents the results of a new approach in the treatment of primary macronodular adrenal hyperplasia (PMAH), with simultaneous total adrenalectomy of the larger adrenal gland and partial adrenalectomy of the contralateral adrenal gland (adrenal-sparing surgery). Materials and Methods We performed a prospective study including 17 patients with PMAH treated surgically with adrenal-sparing surgery i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…It is also known to use image techniques such as scintigraphy to decide which side of adrenal glands to be removed ( 39 ), however, the information is only about the size or hormonal activity of adrenal disease and not able to suggest the partial adrenalectomy. The current evidence regarding the use of partial adrenalectomy is limited ( 40 ). If circulating miRNA expression can predict the subtypes of PBMAH in addition to imaging information, partial adrenalectomy could be adopted more often in cases of multiple adenoma types, which can’t be distinguished from hyperplasia types using scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known to use image techniques such as scintigraphy to decide which side of adrenal glands to be removed ( 39 ), however, the information is only about the size or hormonal activity of adrenal disease and not able to suggest the partial adrenalectomy. The current evidence regarding the use of partial adrenalectomy is limited ( 40 ). If circulating miRNA expression can predict the subtypes of PBMAH in addition to imaging information, partial adrenalectomy could be adopted more often in cases of multiple adenoma types, which can’t be distinguished from hyperplasia types using scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a more promising surgery method was proposed for the treatment of PBMAH, which was called adrenal-sparing surgery. In 2020, Tanno et al [19] first reported this surgery method and demonstrated that most patients undertaken adrenal-sparing surgery had complete hypercortisolism control after 41 months follow-up without the disadvantages of lifetime corticosteroid replacement in a prospective cohort. However, as many patients in this study had mild hypercortisolism, the benefit of this surgery in PBMAH patients with overt CS is needed to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…BA has been taken for the treatment of choice to achieve cure of hypercortisolism [16], but it can result to adrenal insufficiency permanently, requiring lifelong corticosteroid replacement and causing health care burden, including under-and overreplacement associated with increased metabolic risk and adrenal crisis risk, respectively [4]. Considering these negative effects, UA and even adrenal-sparing surgery has been proposed as a promising and safe alternative to BA in patients with mild hypercortisolism or clear adrenal asymmetry [4,[17][18][19]. However, patients with UA or adrenal-sparing surgery may have the risk of recurrence and required a second surgery according to the CS-related manifestations such as uncontrolled hypertension, diabetes, obesity, and dyslipidemia [12], which correlate in part with the extent and duration of cortisol excess [20].…”
Section: Introductionmentioning
confidence: 99%
“…Such patients are prone to acute adrenal crisis as a complication especially under stress or infection, and may have a lower quality of life, so they have to be good compliance 8 12 15 35 . Unilateral total adrenalectomy associated with contralateral partial adrenal (adrenal-sparing surgery) has been observed to achieve good treatment results in PBMAH 55 . This approach avoids the need for lifelong steroid replacement in most cases and has a low rate of adrenal insufficiency and recurrence 56 .…”
Section: Adrenalectomymentioning
confidence: 99%